Molecular characterization of superficial zone chondrocytes under pro-inflammatory and biomechanical stress conditions - Fengrui Liu; Xueting Ding; Pengcui Li; Jie Yuan; Li Guo; Sen Zhao; Gaige Wu; Xiaochun Wei (PLoS ONE, 2026)
Osteoarthritis (OA) is a chronic degenerative joint disease characterized by pathological features such as chondrocyte loss and cartilage matrix degradation. Superficial zone chondrocytes (SFC), located in the outermost layer of articular cartilage and in direct contact with synovial fluid, are the first to respond to mechanical stress and friction. In this study, SFC were isolated and identified in vitro, and their proliferatives and anti-apoptotic properties were examined. Additionally, an early OA inflammatory environment was successfully simulated in cell experiments, demonstrating that inflammatory conditions reduce stemness-associated marker expression in SFC, activate multiple inflammatory pathways, and promote MMP3 expression. When SFC were subjected to cyclic mechanical stretching under inflammatory conditions, increased expression of the mechanosensitive channel Piezo1, enhanced calcium-associated mechanotransduction sensitivity, and disruption of the cytoskeleton were associated with aggravated catabolic responses and apoptosis under inflammatory mechanical stimulation. These findings elucidate the role of SFC in early OA pathogenesis and provide insight into early OA pathogenesis and suggest potential directions for mechanism-based intervention.